Comparison of Thoracic Mobility Against Teenage Smokers and Non-Smokers when Breathing - Martina Puput Ayu Triwanty; Agung Wahyu Permadi; I Made Yoga Parwata (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
Smoking has a bad impact on health because it can lead to death, cardiovascular diseases, as well as diseases of the respiratory system. Thoracic mobility has a very close relationship with respiratory function because the chest wall has an elastic structure that follows movement from the lungs so that pathological changes in the lungs can limit thoracic mobility. Measurement of the mobility of the thoracic cage can be using chest expansion examination. The purpose of this study was to determine the comparison of thoracic mobility to adolescent smokers and non-smokers when breathing. The method used in this study is cross sectional. The results of uji homogeneity using the Levene Test obtained a Sig value of 0.230 so that it can be concluded that the data were taken from homogeneous population variants. The normality test using the Saphiro-Wilk Test in this study obtained Sig values of 0.169 and 0.316 so that it can be concluded that the data are normally distributed. The results of the hypothesis test using the Independent t-Test obtained a Sig value of 0.0000 which showed a significant difference. Based on the results of the research and discussions that have been carried out, the conclusion that can be drawn is that there is a significant difference from the results of measurements that compare the mobility of the thoracic cage to adolescent smokers and non-smokers when breathing.